Anticorrosive and microbial inhibition performance of a coating loaded with Andrographis paniculata on stainless steel in seawater - Wan Mohamad Kamaruzzaman, Wan Mohamad Ikhmal; Mohd Fekeri, Maria Fazira; Mohd Nasir, Nursabrina Amirah; Mohd Hamidi, Nur Aiman Syafiq; Baharom, Mohamad Zahid; Adnan, Azila; Shaifudin, Muhamad Syaizwadi; Wan Abdullah, Wan Rafizah; Wan Nik, Wan Mohd Norsani; Suhailin, Fariza Hanim; Matori, Khamirul Amin; Chen, Soo Kien; et al. (Multidisciplinary Digital Publishing Institute, 2021)
With the trend for green technology, the study focused on utilizing a forgotten herb to produce an eco-friendly coating. Andrographis paniculata or the kalmegh leaves extract (KLE) has been investigated for its abilities in retarding the corrosion process due to its excellent anti-oxidative and antimicrobial properties. Here, KLE was employed as a novel additive in coatings and formulations were made by varying its wt%: 0, 3, 6, 9, and 12. These were applied to stainless steel 316L immersed in seawater for up to 50 days. The samples were characterized and analyzed to measure effectiveness of inhibition of corrosion and microbial growth. The best concentration was revealed to be 6 wt% KLE; it exhibited the highest performance in improving the ionic resistance of the coating and reducing the growth of bacteria.